Superiority Illusion and its relationship with symbolic Self- Completion for Pupils of Distinguished schools (Journal of the College of Basic Education, 2022)
The present Study aims to investigate the following:1.Superiority Illusion for Distinguished schools Pupils.2.Symbolic Self- Completion for Distinguished schools Pupilsstatistically significant relationship in the superiority Illusion and according to the gender variable.Statistically significant differences in the symbolic Self- Completion of outstanding school students according to the gender variable.Between the illusion of excellence in the symbolic Self- Completion of students of schools of excellence. A sample of 300 Distinguished Pupils was chosen randomly for the year 2020-2021. A 30 item superiority Illusion scale was then built according to the definition and theory of Dining and Kroujer. A 26 item symbolic Self perfection scale was also built according to the researcher's definition and the theory of Self- Completion. After finding the psychometric aspects(validity and reliability) to these scales, the were applied to the study's sample.Results showed that the Pupils have both superiority Illusion and symbolic Self- Completion but no statistically significant differences between them in terms of gender. However, the study indicates a posiitive correlative relationship between the two variables. The study ends with some recommendations and suggestions.